COMUNITY STRUCTURE OF GASTROPODS ON MANGROVE AREAS OFSUNGAI RAWA VILLAGE SUBDISTRICT SIAK REGENCY OF RIAU PROVINCE - Mukhlis Alfarys; Efriyeldi Efriyeldi; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The class of gastropods is the largest class in Phylum Molluska. One of the habitat that is inhabited by gastropod is mangrove forest. The structure of the gastropod community of phylum molluska is influenced by changes in environmental factors. This research was conducted in Sungai Rawa Village Subdistrict Siak Regency, in October 2018. The purpose of this research is to know the structure of gastropod community which includes: type, density, diversity, uniformity, dominance, distribution pattern. The characteristics of environmental as sediment type and water quality is considered important for support the research data. The research method used is the survey method where sampling using line transect method was done on 3 stations. 15 gastropods species found in mangrove areas with the value of gastropod density obtained at each research station ranged from6.333-10.667 ind/ha. The value of its diversity index ranges from 2,44-3,07. while the value of uniformity obtained is 0,81-0,86 and the dominance value ranged from 1,29 to 1,95. Characteristics of mangrove area in Sungai Rawa village is good.Kata Kunci:Gastropoda, Community structure, Characteristics